Amazon Forest Ecosystem Responses to Elevated Atmospheric CO2 and Alterations in Nutrient Availability: Filling the Gaps with Model-Experiment Integration - Hofhansl, Florian; Andersen, Kelly M.; Fleischer, Katrin; Fuchslueger, Lucia; Rammig, Anja; Schaap, Karst J.; Valverde-Barrantes, Oscar J.; Lapola, David M. (Frontiers in Earth Science, 2016)
The impacts of elevated CO2 (eCO2) and alterations in nutrient availability on the carbon (C) storage capacity and resilience of the Amazon forest remain highly uncertain. Carbon dynamics are controlled by multiple eco-physiological processes responding to environmental change, but we lack solid experimental evidence, hampering theory development and thus representation in ecosystem models. Here, we present two ecosystem-scale manipulation experiments, to be carried out in the Amazon, that examine tropical ecosystem responses to eCO2 and nutrient addition and thus will elucidate the representation of crucial ecological processes by ecosystem models. We highlight current gaps in our understanding of tropical ecosystem responses to projected global changes in light of the eco-physiological assumptions considered by current ecosystem models. We conclude that a more detailed process-based representation of the spatial (e.g. soil type; plant functional type) and temporal (seasonal and inter-annual variation) diversity of tropical forests is needed to enhance model predictions of ecosystem responses to projected global environmental change.